The philosophers and the Bible: the debate on sacred scripture on early modern thought - Del Prete, Antonella; Schino, Anna Lisa; Totaro, Pina (Brill's studies in intellectual history, 2022)
"The Bible is the breeding ground for the issues nourishing philosophy during the Early Modern age. Different conceptions of God, the world, and the human being have been shaped based on the history of salvation, constructed (or deconstructed) in relation to the various approaches and readings of the Holy Scriptures. This book aims at inquiring the different uses that philosophers made of the Bible. The essays collected in it provide a new perspective on the subject, overcoming the traditional opposition "faith versus science" and enhancing the philosophical approach to the Sacred Scriptures. Philosophers thus promoted a universally recognized moral message and forged the conceptions of the nature, of politics, and of the human being proper to the Early Modern age"--